Perception of the academic training and exigency of university professors focused on the promotion of scientific research - Pino Romero, Neisser (2019)
The academic selection of university teachers has been the basis of the generation of knowledge in the development of scientific development by the development of research among professors and students as a whole. With this, the university education should focus and dedicate the interaction between the scientific, humanistic and social vision of university studies. In recent years he has focused on the prospect of a university education focused on constant research that is related to university students for the generation of knowledge at a scientific and academic level. Therefore, the growth of educational quality is linked to the generation of knowledge and research projects to increase the level of higher education in the country.